2020
DOI: 10.1136/archdischild-2020-318855
|View full text |Cite
|
Sign up to set email alerts
|

Withholding or withdrawing life-sustaining treatment in extremely low gestational age neonates

Abstract: ObjectiveTo identify sociodemographic and clinical factors associated with withholding or withdrawing life-sustaining treatment (WWLST) for extremely low gestational age neonates.DesignObservational study of prospectively collected registry data from 19 National Institute of Child Health and Human Development Neonatal Research Network centres on neonates born at 22–28 weeks gestation who died >12 hours through 120 days of age during 2011–2016. Sociodemographic and clinical factors were compared between infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Our experiences are echoed in the literature which reflects a substantial subset of parents who do not opt to transition their seriously ill infant to comfort-focused care. 24,25 During course development, we created cases in which either continuing survival-focused care or transitioning to comfort-focused care would be ethically acceptable. We predetermined the parent values for each case in order to ensure that course participants would encounter both ‘parents’ whose values would most likely align with comfort-focused care and ‘parents’ whose values would align with ongoing active survival-focused management.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiences are echoed in the literature which reflects a substantial subset of parents who do not opt to transition their seriously ill infant to comfort-focused care. 24,25 During course development, we created cases in which either continuing survival-focused care or transitioning to comfort-focused care would be ethically acceptable. We predetermined the parent values for each case in order to ensure that course participants would encounter both ‘parents’ whose values would most likely align with comfort-focused care and ‘parents’ whose values would align with ongoing active survival-focused management.…”
Section: Discussionmentioning
confidence: 99%
“…Among infants born extremely preterm, National Institute of Child Health and Human Development Neonatal Research Network (NRN) investigators previously found that changes in the rates of many morbidities and in-hospital mortality did not differ by race or ethnicity between 2002 and 2016 . Yet redirection of care occurred more often for non-Hispanic White infants than for non-Hispanic Black infants or for Hispanic infants between 2011 and 2016 . In an overlapping NRN cohort born from 2006 to 2017, neurodevelopmental impairment (NDI) was more common in children who were exposed to maternal SDOH associated with risk or under-resourced status compared to those who were not exposed.…”
Section: Introductionmentioning
confidence: 99%
“…12 Yet redirection of care occurred more often for non-Hispanic White infants than for non-Hispanic Black infants or for Hispanic infants between 2011 and 2016. 13 In an overlapping NRN cohort 14 born from 2006 to 2017, neurodevelopmental impairment (NDI) was more common in children who were exposed to maternal SDOH associated with risk or under-resourced status compared to those who were not exposed. The purpose of the present study was to examine the occurrence of redirection of care discussions and sub-sequent actions for infants born extremely preterm within the context of four SDOH, specifically maternal educational level, insurance type, race, and ethnicity.…”
mentioning
confidence: 99%
“…There are clinical parameters involved in the decision for WLST: GA, IPH extension (bilateral injury, multipolar extension), comorbidities (secondary sepsis, surgery and association with periventricular leukomalacia and/or Papile grade 3 intraventricular haemorrhage (IVH)). However, WLST also differs according to the culture and ethical values of caregivers, parents and countries 11–14…”
Section: Introductionmentioning
confidence: 99%